Electrochemically robust oxide-supported dendritic Pt and Ir nanoparticles for highly effective polymer electrolyte membrane-unitized regenerative fuel cells. Issue 11 (27th February 2023) - Ko, Young-Jin; Kim, Hyunchul; Lee, Woong Hee; Han, Man Ho; Oh, Cheoulwoo; Choi, Chang Hyuck; Kim, Woong; Baik, Jeong Min; Choi, Jae-Young; Strasser, Peter; Oh, Hyung-Suk
Abstract : Electrochemically robust oxide-supported dendritic Pt and Ir nanoparticles for PEM-URFC. Abstract : Polymer electrolyte membrane-unitized regenerative fuel cells (PEM-URFCs) are promising energy storage and conversion systems. However, the dissolution of metal species due to frequent phase transformation and support corrosion at high voltages must be addressed. Herein, we design dendritic Pt (PtND) and Ir (IrND) combined with a robust oxide support (antimony doped tin oxide, ATO) for the oxygen electrode. Under ORR and OER potentials, a PtND–IrND/ATO catalyst produced lower average oxidation states of Pt and Ir than a Pt–Ir/C catalyst. Consequently, the Pt and Ir dissolution of PtND–IrND/ATO derived from the phase transition was significantly less than that of Pt–Ir/C. By investigating the operation factors of the URFC, PtND–IrND/ATO was found to exhibit a high round trip efficiency of 50% at 0.4 A cm −2 with enhanced long-term stability. Our study not only reveals the fundamental reversible catalytic properties of dendritic catalysts, but also offers insights into the catalyst design concept for the oxygen electrode of URFCs.